(untitled) (Actual Problems of Psychology in Educational Institutions, 2018)
The article highlights the views on the frustration reactions of young men, which depend on the style of interpersonal relationships. Everyone experiences frustration differently. It is important that the same frustrator can cause different reactions in different young men. Frustration is a complex emotional and motivational state, manifested by the disorder of activity and communication, resulting from certain insurmountable difficulties that arise in the way of achieving the goal or are an obstacle to the solution of the problem, characteristic of any person. Depending on this, the Leary technique was carried out, which determined the level of the Actual-I and Ideal-I. Differences between these criteria were identified.